(NiSPOLNITELXSKIJ STILX WOKALXNYH PROIZWEDENIJ i(B. (Ns(B. (NbAHAs (NWOPROSY ISTORII(B,(NTEORII(B, (NMETODIKIs - (Nn(B. (NdELICIEWAs ((NmOSKWAs (NmUZYKAs, 1980)
(NkNIGA PRINADLEVIT IZWESTNOMU SPECIALISTU W OBLASTI KAMERNOGO WOKALXNOGO PENIQ(B.s
Keywords: (NMONOGRAFIQs